IDIOMS TRANSLATION STRATEGIES IN PASUNG JIWA NOVEL ENGLISH VERSION - Hariyanto Hariyanto; Amrin Saragih; Sumarsih Sumarsih (LINGUISTIK TERAPAN, 2019)
The research deals with idioms translation strategies. The aims of this study were: (1) to investigate the strategies of translating idioms in Pasung Jiwa novel, (2) to analyze the  process of translation strategies applied in Pasung Jiwa novel, and (3) to describe how the context of idiom translation strategies applied in translating Pasung Jiwa novel. The research was conducted by using qualitative design. The data of this study were words, phrases and clause. The data were collected through documentary technique and the instrument was the documentary sheet. The data were analyzed by using Miles and Huberman’s Interactive Model. The result of this study revealed that: (1) The kinds of idioms translation strategies in Pasung Jiwa Novel found by the researcher namely (a) idiom of similar meaning aand form, (b) idiom of similar meaning but dissimilar form, (c) translating idiom by paraphrase, (d) translating idiom by omission and (e) description strategy. (2) There are four process of idiom translation strategies based on sequences, namely (single process, double process, triple process  and quadruple process) in this study, the most dominant type was single process. triple and quadruple process was not found in this research. (3) From four types of context in translation proposed by Nida (2001), in this study the dominant context was social cultural context. Meanwhile, paralinguistic context and style context were not found. Therefore, in translating idiom, the translators need to know SL/TL culture and its relations to all aspects of cultural background and literature heritage of both languages in translation. The translator wanted the English translated version of Pasung Jiwa Novel easy to understand by the global reader. This translation was aimed to the acceptance of target reader.Keywords: Idioms Translation Strategies, the Contexts of Translation, Pasung Jiwa                  Novel English Version